Um desejo chamado metrópole: a modernização da cidade de Vitória no limiar do século XX - Ferreira, Gilton Luís (2009)
The urban concepts, specially mirrored on the Haussman Baron Parisian model, have influenced several Brazilian cities in the 19th and 20th centuries. The urban restructure turned out to be sought after by city administrators of many Brazilian cities, including Vitória, the administrative capital of Espírito Santo since the Colonial Period. With the advent of the Republic, the colonial past that stamped for a long time its marks on the city architecture would suffer a strong transformation process changing the landscape and urban dynamics of the capixaba capital. The purpose of this study is to present the influence of the modern ideal on the urban restructure of the city of Vitória in the 20th century edge. The empirical research was guided by three corpus documentalis produced between 1890 and 1912: analysis of Government of State Reports, municipality documentation and existing iconography. Therefore, this historiographic study has brought back the genesis of the urban modernization process of the city of Vitória that started in the end of the 19th century and extended to the beginning decades of the 20th century.